Simulation of Fraunhofer Diffraction for Plane Waves using Different Apertures - E. Jallod, Uday. (Iraqi Journal of Science, 2023)
In this paper a two dimensional numerical simulation have been applied usingMATLAB program for generating Fraunhofer diffraction pattern from differentapertures. This pattern is applied for three types of apertures, including, circular,square, and rectangular functions, and it's could be generated any wavelength in thevisible light. The studying demonstrated the capability and the efficiency of opticalimaging systems to observe a point source at very long distance. The circularaperture shows better results across the shape of Fraunhofer pattern and opticaltransfer function (otf). Also, the minimum values of the normalized irradiance ofdifferent diffracted apertures have been computed at different dimensions of theseapertures, and found that the smallest value belongs to the circular aperture andequal to (1.0×10-8) at radius (R=60 pixel).